2022
DOI: 10.1017/s0022226722000445
|View full text |Cite
|
Sign up to set email alerts
|

Factivity and complementizer omission in English embedded gapping

Abstract: Taking as a starting point the variation in introspective judgments on embedded gapping in English in the literature, the main goal of this paper is to test the ‘No Embedding Constraint’ experimentally. Building on a first experimental study designed to measure the interaction between that-omission and factivity in English embedded complement clauses, we conducted two experiments testing the role of the complementizer in embedded gapping, paying special attention to the semantic nature of the matrix predicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…We looked at the subset of the verbs from our Surveys A and B which are listed as either factive or semi-factive in Hooper ( 1975 ) and Hooper and Thompson ( 1973 ) and compared these with those which are listed by these authors listed as non-factive. Consistent with Bîlbîie et al ( 2023 ) we found that the non-factive verbs ( think , say , believe , suggest , guess , suppose , insist , admit , figure , state , claim , imagine , agree , indicate , point out , argue , presume , demonstrate , assert , maintain , affirm , remark , contend , intimate , hypothesize , predict , divulge ) yielded a lower rate of that -mention (11.7%) compared with the subset characterized as factive or semi-factive ( know , remember , realize , notice , find out , discover , note , reveal ; 29.5%). This is line with our earlier discussion of non-homogeneity of that -optionality across different kinds of embedding verbs ( Introduction ).…”
Section: Evaluating the Proposalsupporting
confidence: 87%
See 4 more Smart Citations
“…We looked at the subset of the verbs from our Surveys A and B which are listed as either factive or semi-factive in Hooper ( 1975 ) and Hooper and Thompson ( 1973 ) and compared these with those which are listed by these authors listed as non-factive. Consistent with Bîlbîie et al ( 2023 ) we found that the non-factive verbs ( think , say , believe , suggest , guess , suppose , insist , admit , figure , state , claim , imagine , agree , indicate , point out , argue , presume , demonstrate , assert , maintain , affirm , remark , contend , intimate , hypothesize , predict , divulge ) yielded a lower rate of that -mention (11.7%) compared with the subset characterized as factive or semi-factive ( know , remember , realize , notice , find out , discover , note , reveal ; 29.5%). This is line with our earlier discussion of non-homogeneity of that -optionality across different kinds of embedding verbs ( Introduction ).…”
Section: Evaluating the Proposalsupporting
confidence: 87%
“…On the other hand, verbs like regret are factive, because they presuppose that the proposition in the embedded clause is true. Recent experimental work has found that embedded clause complements of factive verbs are judged by speakers of English to be less acceptable with that -omission as compared non-factive verbs (Bîlbîie et al, 2023 ), indicating that factivity is a key factor in conditioning acceptability of that -omission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations